Outcomes of paroxysmal nocturnal hemoglobinuria in the pediatric age group in a resource‐constrained setting. Issue 4 (26th March 2019) - Halder, Rohan; Mishra, Priyanka; Aggarwal, Mukul; Mannivanan, Prabhu; Dhawan, Rishi; Seth, Tulika; Tyagi, Seema; Mahapatra, Manoranjan; Pati, Hara P.; Saxena, Renu
Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired clonal stem cell disorder. Eculizumab and bone marrow transplantation are disease‐modifying treatments for PNH but may not be readily available in resource‐constrained settings. Of 52 pediatric patients with PNH, 20 had classical PNH and 32 had PNH/aplastic anemia (PNH/AA). Median time to diagnosis was 30 months in classical PNH patients. Renal failure was present in four patients (20%). Six (30%) achieved complete response, 10 (50%) achieved partial response with androgens in classical PNH. Two underwent allogenic stem cell transplantation. In the PNH/AA group, 16 (50%) were in CR and seven (21%) were in PR with anti‐thymocyte globulin ± cyclosporine.